Islam Rahmatan Lil’alamin - Alexa, Silvani; Rezahraini, Sabrina; Syukri Azhari, Devi (UNIVERSITAS SERAMBI MEKKAH, 2025)
The concept of Islam as Rahmatan lil ‘Alamin is a fundamental principle that emphasizes Islam as a mercy for all of creation, including humans, the environment, and other beings. This study aims to analyze the concept of Rahmatan lil ‘Alamin from the perspective of the Qur'an and Hadith and its implementation in social life. The research method used is a qualitative approach with a library research study, involving an analysis of primary sources such as the Qur'an, Hadith, and scholarly literature from Muslim scholars. The findings indicate that Islam promotes values of compassion, tolerance, justice, and universal well-being, which are relevant to modern challenges. Thus, the concept of Rahmatan lil ‘Alamin can serve as a solution for fostering social harmony and global peace.